Online purchase intentions of affluent women: blending African beliefs, consumer vanity and luxury beauty products online purchase intentions - Jaravaza, Divaries C; Mukucha. Paul; Nhidza, Lucy; Makudza, Forbes (Cogent Social Sciences, 2025)
With the growing popularity of online shopping and the increasing demand for luxury beauty products, understanding the underlying cultural factors influencing consumer behaviour becomes crucial for marketers and researchers alike. This study aims to investigate the influence of African social axioms on affluent women’s consumer vanity and luxury beauty products online purchase intention in Zimbabwe. Data was collected from 400 affluent female respondents in Zimbabwe through convenience sampling. The study used a structured questionnaire to gather information from affluent women in affluent suburbs and shopping centres. Data was analysed using structural equation modelling on SPSS AMOS. Findings of the study revealed significant negative relations between Ubuntu and consumer vanity. Other African beliefs of ancestral relevance and religiosity had positive relations to consumer vanity. Consumer vanity had positive relations to online purchase intentions of luxury beauty products. It was also concluded that individuals who place importance on their ancestral heritage and strong religious beliefs may be more inclined to prioritise physical appearance leading to a greater interest in luxury beauty products. However, individuals who uphold Ubuntu ethos are least concerned with vanity, hence, promotional messages and branding must incorporate Ubuntu to capture such consumers.
Keywords: Affluent women; Ubuntu; religiosity; consumer vanity; luxury beauty products; online purchase intentions